TEORI IDENTITAS SOSIAL, STEREOTIPE & PRASANGKA - Ane Novella WF; Nevriyarni S (PT. Hasba Edukasi Mandiri, 2026)
In an increasingly pluralistic modern society, interactions between individuals from various social, cultural, and ethnic backgrounds present both opportunities and challenges in maintaining social harmony. This article aims to examine the relationship between social identity, stereotypes, and social prejudice through a systematic literature review of recent empirical and theoretical research. Based on Social Identity Theory (Tajfel & Turner, 1979), group identity is an important basis for forming self-perceptions and attitudes toward other groups. This social categorization process often gives rise to in-group favoritism and out-group bias, which then become the root of the emergence of stereotypes and social prejudice. The results of this study indicate that stereotypes act as cognitive mechanisms that simplify social reality, but also reinforce bias and discrimination, particularly through digital media and existing social structures. Meanwhile, social prejudice is a negative affective expression toward other groups that has a broad impact on psychological well-being and intergroup relations. Contemporary studies confirm that interventions based on empathy, perspective-taking, and the contact hypothesis (Allport, 1954; Pettigrew & Tropp, 2011) are effective in reducing prejudice and increasing social inclusiveness. This article emphasizes that managing complex and inclusive social identities is key to building a more tolerant and harmonious society in the era of globalization and digitalization.